2015
DOI: 10.1007/s00707-015-1484-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of base excitation frequency on the stability of a freestanding rigid block

Abstract: The behavior of a freestanding block subjected to base excitation is a nonlinear problem. In the past, many researchers have analyzed freestanding blocks subjected to base excitation and reported their findings. However, still more understanding is required to understand excitation frequency effects on the stability of a freestanding block. Detailed experiments and numerical analysis were performed on a parallelepiped block having an aspect ratio of four, for different values of coefficient of friction and bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The response of a rigid block resting on a foundation with a periodic excitation has been studied [2] and is found not to slip when the frequency ratio exceeds one. The effect of base excitation frequency on a free-standing rigid block [3] has been studied, and it was found that base excitation frequency plays a vital role in determining the stability of rigid blocks. Sliding displacement of an unanchored body subjected to earthquake excitation is estimated [4].…”
Section: Introductionmentioning
confidence: 99%
“…The response of a rigid block resting on a foundation with a periodic excitation has been studied [2] and is found not to slip when the frequency ratio exceeds one. The effect of base excitation frequency on a free-standing rigid block [3] has been studied, and it was found that base excitation frequency plays a vital role in determining the stability of rigid blocks. Sliding displacement of an unanchored body subjected to earthquake excitation is estimated [4].…”
Section: Introductionmentioning
confidence: 99%